Being Heard: Motivating Millennials Through Multiple Intelligences (Journal on Excellence in College Teaching, 2024)
In today's instant gratification era, it is easy to assume that when faced with the option of reading a chunky literary text or skimming through the condensed electronic version, students will take the path of least resistance. Today's e-guides are quick, painless, and free. The question, then, becomes this: Knowing these e-resources are readily available and will be accessed frequently, how can we encourage students to think outside the box in order to liven up classroom discussions and encourage critical-thinking strategies (Edwards, 2012)? This essay will argue that students of this generation need both (a) a voice of their own and (b) new pedagogies that address all of the senses in order to cultivate engaged reading and interpretation. One of the ways to facilitate this is meshing the old with the new, specifically by revisiting group work.